2019
DOI: 10.32014/2019.2518-170x.65
|View full text |Cite
|
Sign up to set email alerts
|

Change of Formation Conditions of Groundwater of Kazakhstan Under the Influence of Anthropogenic Changes of the Environment

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Research related to the selection of ground water recharge areas has been carried out by many researchers. Osipov et al [16] investigated changes in the groundwater formation in Kazakhstan. This study found that the groundwater in Kazakhstan is influenced by several factors such as natural factors, climate, the geological structure, and the human activities.…”
mentioning
confidence: 99%
“…Research related to the selection of ground water recharge areas has been carried out by many researchers. Osipov et al [16] investigated changes in the groundwater formation in Kazakhstan. This study found that the groundwater in Kazakhstan is influenced by several factors such as natural factors, climate, the geological structure, and the human activities.…”
mentioning
confidence: 99%